Climbing The Stratification Ladder and The Decreasing of Small Entrepreneurs Number In The Field of ASGM In North Minahasa, North Sulawesi - Purwanto, Antonius (Masyarakat: Jurnal Sosiologi, 2020)
This article is the result of research on artisanal and small-scale gold mining in Tatelu. The study was conducted using field theory and qualitative research methods. With the permission from the government, mining activities become stable because there is certainty of ownership rights. Mining activities are managed by entrepreneurs, cooperatives, and the village government and have provided welfare for the people of Tatelu and surrounding areas. Villagers involved in mining have transformed economic capital obtained from mining into physical capital in the form of village infrastructure, housing, cultural or educational capital, and investment in other economic activities. There is vertical mobility of several miners and entrepreneurs. Vertical mobility begins after mining activities are stable where the agency capacity of the actors can be realized in the form of actions that allow capital accumulation. The deeper the hole to get gold ore, the more difficult the upward mobility of miners and entrepreneurs with limited economic capital because mining costs are increasingly expensive. There are indications that entrepreneurs with small capital will decrease because they cannot finance the mining business. The results of this study will lead to the conclusion that in the field of small scale mining economic capital is far more decisive than cultural capital and the agency capacity of the actors is increasingly limited as the mine hole deepens.